TRADITIONAL GAMES AND SOCIAL SKILLS OF CHILDREN IN THE PANDEMIC ERA - Masnur Ali; Hartman Nugraha; Qory Jumrotul Aqobah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractThe purpose of this research is to study and analyze about the traditional games that can be played in-home environment that can help early childhood social development. Children's social skills are not just suddenly formed but it is from imitation and habituation of the child's closest environment, namely family. In this pandemic era, of course, the learning in early childhood is mostly done in-home environment, to prevent boredom and improving children's activity requires efforts from the family to be able to carry out physical activities. The traditional games besides of being safe to play from various ages, it is a characteristic of the nation's culture which has various benefits and values that can be developed, including social skills. The research method in this research is library research. Some traditional games can be introduced from early childhood in the family environment to introduce traditional games and children's social development. From the results of the analysis in previous studies, traditional games can stimulate the development of children's social skills. Keywords: Social development, traditional games